Beginning PHP and Oracle - Gilmore, W. Jason (Apress, 2012)
Mahatma Gandhi once famously said, “First they ignore you, then they laugh at you, then they fight you, then you win.” Although there’s not yet any clear winner, the software industry seems to be following a similar path. Although the open source movement began back in the 1970s due to Richard Stallman’s printer-borne frustrations in an MIT computer lab, it wasn’t until the late 1990s that the community-driven approach to software development began to make any significant waves in the business environment. And with it came gasps of both horror and hilarity among the proprietary software elite. After all, a bunch of volunteers could hardly produce code of a quality approaching, let alone surpassing, that which is built in the hallowed cathedrals of software development, right? Such guffaws rang increasingly loudly despite numerous clear successes in the open source community, such as the Apache dominating position in the Web server market and Linux’s meteoric rise to become one of the world’s most popular operating systems. But soon it became apparent this approach did work after all, as was evidenced by the rapid adoption of open source solutions for commonplace tasks such as code editing, FTP transfer, file compression, databasing, and word processing. The commercial software industry responded with overt attempts to discredit the competing open source competitors, highlighting feature deficiencies, scaling problems, lack of traditional user support, and anything else that would justify its products’ often hefty price tags.